Effects of listening to music in digestive endoscopy: A prospective intervention study led by nursing. (9th September 2020) - Spagnuolo, Rocco; Corea, Alessandro; Blumetti, Mariantonietta; Giovinazzo, Alessia; Serafino, Massimiliano; Pagliuso, Caterina; Pagnotta, Raffaele; Curto, Grazia; Cosco, Cristina; Cosco, Vincenzo; Mancina, Rosellina Margherita; Garieri, Pietro; et al.
Abstract: Aims: To explore whether music can reduce anxiety and pain in patients who underwent diagnostic endoscopic examinations in conscious and deep sedation and to assess degree of satisfaction and willingness to repeat the procedure. Design: Prospective study led by nursing. Methods: Between March 2019–June 2019, consecutive outpatients undergoing endoscopic examinations were simple matched into four groups: Group 1: conscious sedation with music; Group 2: conscious sedation without music; Group 3: deep sedation with music and Group 4: deep sedation without music. Ten minutes before the procedure, two trainee nurses applied music. State‐Trait Anxiety Inventory was used to evaluate anxiety. Results: Before and at the end of the procedure, patients who listened to music had a lower level anxiety than those who did not listen and, also, reported lower pain intensity during procedure. Only within Group 1 median anxiety, measured after the procedure, is lower than that measured before. In the bivariate logistic regression model, pain and listening to music were independent factors for satisfaction and willingness to repeat procedure. Conclusion: music in digestive endoscopy reduce pain and anxiety in conscious sedation, thus could be used to reduce anxiety in support to conscious sedation leading to lower usage of deep sedation and consequently reduction of costs and adverse events. Impact: Anxiety in digestive endoscopy limits patients' satisfaction. Music in digestive endoscopy as a specific nursing intervention could reduce anxiety of patients. This nursing intervention study confirms positive effect of music in digestive endoscopy. As part of nursing management, the addition of music to daily care practice in digestive endoscopy may reduce anxiety and increase the patient's degree of satisfaction. Use of music could limit deep sedation use in digestive endoscopy with consequent reduction of risks for patients, execution times, and costs of procedures. 摘要: 目标: 探讨音乐能否减轻在清醒和深度镇静下接受内镜诊断检查的患者的焦虑和疼痛, 并评估患者的满意度和重复检查的意愿。 设计: 以护理学为主导的前瞻性研究。 方法: 将在2019年3月至2019年6月期间接受内窥镜检查的例门诊患者简单地分为四组:第一组:清醒镇静状态下听音乐;第二组:清醒镇静状态下不听音乐;第三组:深度镇静状态下听音乐;第四组:深度镇静状态下不听音乐。术前10分钟由两名实习护士播放音乐。采用 状态-特质焦虑问卷 评价焦虑程度。 结果: 在术前和术后, 听音乐的患者比不听音乐的患者的焦虑程度更低, 且术中的疼痛强度也更低。只有第1组术后测得焦虑程度为中度, 比术前测得的程度略低。在双变量逻辑回归模型中, 疼痛和听音乐是满意度和重复检查意愿的两个独立因素。 结论: 在消化内镜检查中听音乐可以减少清醒镇静时的疼痛和焦虑感, 因此可以用来减少支持清醒镇静的焦虑程度, 从而减少深度镇静的运用, 藉此降低成本和不良事件。 影响: 消化内镜检查中的焦虑会限制患者的满意度。 在消化内镜检查中听音乐作为一种特殊的护理干预措施可以降低患者的焦虑感。 该护理干预措施研究证实在消化内镜检查中听音乐具有积极的作用。 作为护理管理的一部分, 在消化内镜的日常护理实践中加入音乐可以减少焦虑感, 提高患者的满意度。 使用音乐可以控制消化内镜检查中的深度镇静的运用, 从而降低患者的风险、实施时间和成本。